FgCDC14 regulates cytokinesis, morphogenesis, and pathogenesis in Fusarium graminearum. Issue 4 (10th September 2015) - Li, Chaohui; Melesse, Michael; Zhang, Shijie; Hao, ChaoFeng; Wang, Chenfang; Zhang, Hongchang; Hall, Mark C.; Xu, Jin‐Rong
Summary: Members of Cdc14 phosphatases are common in animals and fungi, but absent in plants. Although its orthologs are conserved in plant pathogenic fungi, their functions during infection are not clear. In this study, we showed that the CDC 14 ortholog is important for pathogenesis and morphogenesis in F usarium graminearum . FgCDC 14 is required for normal cell division and septum formation and FgCdc14 possesses phosphatase activity with specificity for a subset of Cdk‐type phosphorylation sites. The F gcdc14 mutant was reduced in growth, conidiation, and ascospore formation. It was defective in ascosporogenesis and pathogenesis. Septation in F gcdc14 was reduced and hyphal compartments contained multiple nuclei, indicating defects in the coordination between nuclear division and cytokinesis. Interestingly, foot cells of mutant conidia often differentiated into conidiogenous cells, resulting in the production of inter‐connected conidia. In the interphase, FgCdc14‐GFP localized to the nucleus and spindle‐pole‐body. Taken together, our results indicate that Cdc14 phosphatase functions in cell division and septum formation in F . graminearum, likely by counteracting Cdk phosphorylation, and is required for plant infection. Abstract : The CDC14 phosphatase is important for regulating septation and mitotic exit in the wheat scab fungus Fusarium graminearum . The Fgcdc14 deletion mutant is irregular in septum formation and has multiple nuclei in intercalary conidium compartments. It also often produces inter‐connected conidia that may be caused by its defects in cell division and cytokinesis.